Passenger kilometer traveled of the express buses in Malaysia - Ab. Hadi, Karim (2008)
It is the time for Malaysia to move forward to a certain level by having a variety and reliable road safety indicators. Study on passenger kilometer traveled specifically for express buses in Malaysia maybe relatively small effort but very significant step and meaningful contribution towards road safety development in Malaysia. This study intends to develop another road accident fatality indicator .i.e. fatality per billion passenger kilometer traveled (PKT) for road transport in Malaysia. Since passenger and distance traveled are the main components of risk exposure, therefore PKT is seen to be more appropriate road safety indicator especially related to fatality and injuries involving occupants of the vehicles. It is hoped that further research or study especially those related to passenger kilometer traveled could be benefited from this study. The conventional method of data collection in terms of travel data and traffic casualties was employed. Secondary data required for analysis were obtained mainly from the bus operators and police records. To ensure data has significant level of confidence,validation and verification measures were carried out through statistics approaches and use of the latest technology such as GPS for verification purpose. Analysis was carried out using two different approaches with intention to compare the results obtained from each method. Fatality per billion passenger kilometer traveled (PKT) depends on the reliability of the number of fatality and the accuracy of the passenger kilometer traveled estimation. Based on the study finding the estimated PKT value of express bus in Malaysia in 2007 was 25.05 billion. Using this estimated PKT value together with estimated fatality of 26 specifically involving drivers and passengers of express buses in 2007, it is therefore estimated that fatality per billion PKT of the express buses in Malaysia in 2007 was 1.04.